Understanding the Water Balance of Basement Complex Areas in Sokoto Basin, North-West Nigeria for improved Groundwater Management - Abubakar Gada, Murtala (Cranfield University, 2014)
Understanding water balances is essential for sustainable water resource management, especially in semi-arid basement complex areas where there are large demands for water supplies, but the complex hydrogeological conditions limit groundwater development. This research presents an approach for water balance estimation based on the conceptual and computational modelling of six major landscape unit’s which have been classified on the basis of their differing hydrological responses. Detailed conceptual models of the hydrological processes operating in each of the different landscapes in a catchment and the processes that control water movement between the different landscapes are developed based on data analysis, fieldwork and literature. Two computational models (the WaSim soil water balance model and a new water balance model for bare rock) are used to estimate the daily water balance of each of the landscape units taking cognisance of their interconnectivity which includes runoff becoming run-on. Water balance simulations were run for the individual landscapes using input data from the semi-arid Sokoto Basin in Northwest Nigeria, and outputs for representative wet and dry years are used to demonstrate the reliability of model responses. The individual landscapes outputs were subsequently integrated, taking account of their area weighted contributions, to give a catchment-scale water balance which compares favourably with the observed river discharge at Fokku. The catchment water balance results reveal that AET accounts for the largest loss in the catchment at 72 % of the average rainfall for 37 years. This is followed by the groundwater flow to rivers, then runoff to rivers, representing 16% and 11 % of the average rainfall. This research has provided valuable insights into hydrological behaviour of the basement complex system and the effect of landscape variability on the water balance of these areas. The research suggested a rational approach to groundwater resource management in the basement complex areas that takes cognizance of the hydrological behaviour of different landscape units, focussing on areas with deep weathered material within the catchment identified in this research. The research specifically stresses the need to apply methods of water conservation during excess rainfall for future use in the dry season.
Keywords: WaSim; Water Balance; Basement Complex; Landscape Units; Groundwater Management